Essential University Physics: Volume 1 (3rd Edition)

Published by Pearson
ISBN 10: 0321993721
ISBN 13: 978-0-32199-372-4

Chapter 18 - Exercises and Problems - Page 332: 71


The proof is below.

Work Step by Step

We know the following: $P_1V_1^{\gamma} = P_2V_2^{\gamma} $ We use the ideal gas law to find: $p_1=\frac{RT_1}{V_1}$ $p_2=\frac{RT_2}{V_2}$ Combining these three equations gives: $\frac{RT_1}{V_1}V_1^{\gamma} =\frac{RT_2}{V_2}V_2^{\gamma} $ $T_1V_1^{\gamma-1}=T_2V_2^{\gamma-1} $ $T_1V_1^{\gamma-1}=k$ Where k is a constant.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.